The Correlation Between Dental Caries And Nutritional Status In Children Between The Ages Of Three And Five - Yanik Purwanti; Hesty Widowati; Windy Yuliartanti (PT. Anagata Sembagi Education, 2024)
Data from the Indonesian Ministry of Health in 2018 indicate that only 7% of children in Indonesia are cavity-free, while a staggering 93% of children under the age of three experience dental caries. The pathological process known as tooth decay is characterized by damage restricted to the hard tissues of the tooth, starting with the enamel and progressing to the dentin. Nutritional status, which can be classified as adequate, inadequate, poor, or stunted, plays a crucial role in the overall health of children, including their oral health. This study aims to investigate the relationship between dental caries levels and nutritional status among preschool children at Aisyiyah Kindergarten/RA Kemantren Tulangan, Sidoarjo. The study employs a cross-sectional methodology and adopts an analytical survey approach. The sample used in this research consists of a total sampling of sixty individuals. The def-t index is utilized as the measuring tool to evaluate the presence of cavities, while the PB/U or TB/U index is used to determine the short nutritional status based on the WHO Anthro 2005 reference standards. Data analysis is conducted using SPSS, where a Chi-square test is performed to ascertain the association between the degree of dental caries in preschool-aged children and their nutritional status. The results of the study are presented in both tabular and narrative forms to provide a comprehensive overview of the relationships identified. This research is expected to contribute to a deeper understanding of the importance of proper dental care and nutrition in promoting the health of young children